Preparation of breadfruit starch nanoparticle: usage of nanoprecipitation method and the application in Pickering emulsion - Bovi Wira Harsanto (Universitas Veteran Bangun Nusantara, 2023)
Breadfruit is one of the agricultural products with high starch content (> 20%), leading to the potential for starch source. The limitation of native breadfruit starch (NBS) in the application of Pickering emulsion was the main reason for preparing breadfruit starch nanoparticles in this research. Preparation of breadfruit starch nanoparticles with the nanoprecipitation method was a time-efficient method. Therefore, this research aimed to evaluate breadfruit starch nanoparticle preparation (BSN) in the nanoprecipitation method and its application in Pickering emulsion. Investigation of size and shape, FTIR profile, turbidity as well as visual appearance and creaming index of Pickering emulsion was conducted to support and confirm the objective of this research. This study found that micrometer scale, high hydroxyl groups, high turbidity of NBS were altered into the nanoscale, low hydroxyl groups, and low turbidity of BSN leading to the successful indication of preparation of breadfruit starch nanoparticle with nanoprecipitation method. The stability of Pickering emulsion improved with breadfruit starch nanoparticles, indicated by physical appearance and creaming index for 7-day storage at room temperature.